2000
DOI: 10.1159/000054078
|View full text |Cite
|
Sign up to set email alerts
|

Signalling Pathways Activated by 5-HT<sub>1B</sub>/5-HT<sub>1D</sub> Receptors in Native Smooth Muscle and Primary Cultures of Rabbit Renal Artery Smooth Muscle Cells

Abstract: The potential of primary cultures of rabbit renal artery vascular smooth muscle cells (VSMCs) was assessed as a means to investigate the signalling pathways linked to 5-hydroxytryptamine (5-HT) 5-HT1B/5-HT1D receptors in native arteries. In renal artery segments denuded of endothelium, incubated with ketanserin and prazosin (each 1 µM), and prestimulated with 20 mM K+ Krebs buffer, 5-HT and CP 93,129, a 5-HT1B receptor agonist, evoked concentration-dependent contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…These results indicate that the roles of 5-HT 1B/D and 5HT 2A receptors are unaffected by LTH stress. Moreover, the relative potency of these antagonists indicates that 5-HT 2A receptors, which are commonly coupled with Gq proteins and linked to contractility via Ca 2 + -dependent signaling pathways, are of greater importance than 5-HT 1B/D receptors, which are coupled through G i mechanisms (Hinton et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the roles of 5-HT 1B/D and 5HT 2A receptors are unaffected by LTH stress. Moreover, the relative potency of these antagonists indicates that 5-HT 2A receptors, which are commonly coupled with Gq proteins and linked to contractility via Ca 2 + -dependent signaling pathways, are of greater importance than 5-HT 1B/D receptors, which are coupled through G i mechanisms (Hinton et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, 5-HT 1D /1B receptors are negatively coupled to adenylyl cyclase, a transduction mechanism associated with the inhibition of the release of neurotransmitters, and it is known that pre-junctional 5-HT 1D /1B receptor activation inhibits noradrenaline release from vascular sympathetic nerve terminals (see Hoyer et al 1994). Recently, however, different studies have suggested that other signalling pathways different from adenylyl cyclase inhibition, such as mitogen-activated protein kinase activation, would be linked to this receptor subtype (Hinton et al 2000;Albert & Tiberi 2001;Watts et al 2001). In particular, the studies of Lin et al (2002) provide evidence that although all 5-HT 1 receptors negatively regulate adenylyl cyclase to some extent, they differentially couple to G proteins and consequently exhibit differences in coupling to cellular signals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 5-HT induced ERK1/2 activation in rat aortic smooth muscle cells and rabbit isolated renal artery smooth muscle cells [9,10] . However, whether the intracelluar signal pathway of 5-HT in PASMCs is dependent on the ERKs activation is largely unconcerned.…”
Section: Introductionmentioning
confidence: 94%